Ralstonia solanacearum fatty acid composition is determined by interaction of two 3-ketoacyl-acyl carrier protein reductases encoded on separate replicons. Issue 1 (December 2015) - Feng, Sai-Xiang; Ma, Jin-Cheng; Yang, Ji; Hu, Zhe; Zhu, Lei; Bi, Hong-Kai; Sun, Yi-Rong; Wang, Hai-Hong
Abstract Background FabG is the only known enzyme that catalyzes reduction of the 3-ketoacyl-ACP intermediates of bacterial fatty acid synthetic pathways. However, there are twoRalstonia solanacearum genes, RSc1052 (fabG1 ) and RSp0359 (fabG2 ), annotated as encoding putative 3-ketoacyl-ACP reductases. Both FabG homologues possess the conserved catalytic triad and the N-terminal cofactor binding sequence of the short chain dehydrogenase/reductase (SDR) family. Thus, it seems reasonable to hypothesize thatRsfabG1 andRsfabG2 both encode functional 3-ketoacyl-ACP reductases and play important roles inR. solanacearum fatty acid synthesis and growth. Methods Complementation ofEscherichia coli fabG temperature-sensitive mutant withR. solanacearum fabGs encoded plasmids was carried out to test the function ofRsfabGs in fatty acid biosynthesis. RsFabGs proteins were purified by nickel chelate chromatography and fatty acid biosynthetic reaction was reconstituted to investigate the 3-ketoacyl-ACP reductase activity of RsFabGsin vitro . Disruption of bothRsfabG genes was done via DNA homologous recombination to test the function of bothRsfabG in vivo . And more we also carried out pathogenicity tests on tomato plants using RsfabG mutant strains.  Results We report that expression of either of the two proteins (RsFabG1 and RsFabG2) restores growth of theE. coli fabG temperature-sensitive mutant CL104 under non-permissive conditions.In vitro assays demonstrate that both proteins restore fatty acid synthetic ability to extracts of theE. coli strain. TheRsfabG1 gene carried on theR. solanacearum chromosome is essential for growth of the bacterium, as is the case forfabG inE. coli . In contrast, the null mutant strain with the megaplasmid-encodedRsfabG2 gene is viable but has a fatty acid composition that differs significantly from that of the wild type strain. Our study also shows that RsFabG2 plays a role in adaptation to high salt concentration and low pH, and in pathogenesis of disease in tomato plants. Conclusion R. solanacearum encodes two 3-ketoacyl-ACP reductases that both have functions in fatty acid synthesis. We supply the first evidence that, like other enzymes in the bacterial fatty acid biosynthetic pathway, one bacterium may simultaneously possess two or more 3-oxoacyl-ACP reductase isozymes.